2015
DOI: 10.1016/j.pedneo.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Endocan and Soluble Triggering Receptor Expressed on Myeloid Cells-1 as Novel Markers for Neonatal Sepsis

Abstract: Serum sTREM-1, IL-6, endocan levels, and I/T ratio increased in septic neonates. However, the diagnostic accuracy of circulating sTREM-1 seemed to be better than endocan and I/T ratio, but lower than IL-6.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 24 publications
3
49
0
2
Order By: Relevance
“…In our study, we found that sTREM-1 levels showed highly significant statistical decrease 48-72 hrs after administration of antibiotics in relation to initial sTREM-1 levels indicating that sTREM-1 is a useful monitoring marker for follow-up of septic neonates to observe the effect of treatment which is consistent with the results of Sarafidis et al (2010) and Saldir et al (2015). The main limitation in our study was small sized sample number which can be validated by further large scale studies before application to general population.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In our study, we found that sTREM-1 levels showed highly significant statistical decrease 48-72 hrs after administration of antibiotics in relation to initial sTREM-1 levels indicating that sTREM-1 is a useful monitoring marker for follow-up of septic neonates to observe the effect of treatment which is consistent with the results of Sarafidis et al (2010) and Saldir et al (2015). The main limitation in our study was small sized sample number which can be validated by further large scale studies before application to general population.…”
supporting
confidence: 86%
“…Although several studies documented the role of serum level of sTREM-1 in diagnosis of neonatal sepsis (Su et al, 2012;Saldir et al, 2015), there is insufficient data regarding its prognostic value in neonatal sepsis. Hence, our study aimed at investigating the role of serum levels of sTREM-1 in early diagnosis and prognosis of LOS.…”
Section: Int J Adv Res 4(8) 123-131 124mentioning
confidence: 99%
“…PCT serum levels rise faster than CRP, but the initial reports of sensitivity close to 100% have not been confirmed by subsequent evaluations [15,19,20]. The complex pathophysiological mechanisms of sepsis involve inflammation and endothelial activation as critical determinants of the host response, leading to the hypothesis that biomarkers of endothelium dysfunction might be used as clinical tools in the diagnosis and follow-up of sepsis [21].…”
Section: Discussionmentioning
confidence: 99%
“…sTREM-1 is under investigation as a biomarker in a variety of infectious and non-infectious inflammatory conditions and is detected in the bronchoalveolar lavage (BAL) fluid in pneumonia 7 and in the serum 8,9 and urine 10 of septic patients. It is a marker of neonatal sepsis 11 and predicts shock and death. 12 sTREM-1 and its gene polymorphisms are also associated with sepsis prognosis 13 and high sTREM-1 is predictive of Systemic Inflammatory Response Syndrome (SIRS) 14 after surgery.…”
Section: Introductionmentioning
confidence: 99%